Global Health and Emergency Care: Defining Clinical Research Priorities. (17th March 2017) - Hansoti, Bhakti; Aluisio, Adam R.; Barry, Meagan A.; Davey, Kevin; Lentz, Brian A.; Modi, Payal; Newberry, Jennifer A.; Patel, Melissa H.; Smith, Tricia A.; Vinograd, Alexandra M.; Levine, Adam C.; ,
Abstract: Objectives: Despite recent strides in the development of global emergency medicine (EM), the field continues to lag in applying a scientific approach to identifying critical knowledge gaps and advancing evidence‐based solutions to clinical and public health problems seen in emergency departments (EDs) worldwide. Here, progress on the global EM research agenda created at the 2013 Academic Emergency Medicine Global Health and Emergency Care Consensus Conference is evaluated and critical areas for future development in emergency care research internationally are identified. Methods: A retrospective review of all studies compiled in the Global Emergency Medicine Literature Review (GEMLR) database from 2013 through 2015 was conducted. Articles were categorized and analyzed using descriptive quantitative measures and structured data matrices. The Global Emergency Medicine Think Tank Clinical Research Working Group at the Society for Academic Emergency Medicine 2016 Annual Meeting then further conceptualized and defined global EM research priorities utilizing consensus‐based decision making. Results: Research trends in global EM research published between 2013 and 2015 show a predominance of observational studies relative to interventional or descriptive studies, with the majority of research conducted in the inpatient setting in comparison to the ED or prehospital setting. Studies on communicable diseases and injury were the most prevalent, with a relative dearth of research on chronic noncommunicable diseases. The Global Emergency Medicine Think Tank Clinical Research Working Group identified conceptual frameworks to define high‐impact research priorities, including the traditional approach of using global burden of disease to define priorities and the impact of EM on individual clinical care and public health opportunities. EM research is also described through a population lens approach, including gender, pediatrics, and migrant and refugee health. Conclusions: Despite recent strides in global EM research and a proliferation of scholarly output in the field, further work is required to advocate for and inform research priorities in global EM. The priorities outlined in this paper aim to guide future research in the field, with the goal of advancing the development of EM worldwide.